Natural Numbers Division: from predicted knowledge to knowledge effectively taught in elementary school classes - Cruz, José André Bezerra da; Teles , Rosinalda Aurora de Melo (Educação Matemática Debate, 2020)
This article is an excerpt from an academic master's research that adopts the notion of didactic transposition by Yves Chevallard and aims to analyze aspects related to the internal didactic transposition process of the natural numbers division operation in elementary school. To support the analysis of the mathematics classes of three teachers, a study of the legal documents of Brazil and the State of Pernambuco was carried out, thus being analysis of textbooks for the 4th, 5th and 6th years and interviews with the teachers who work in those school years. Within the classes, the focus of analysis was the different meanings of the division, the calculation procedures, the treatment given to the rest and the interpretation of the results obtained, addressed or not into the observed classes. When comparing the knowledge expected to be taught and the knowledge effectively taught, changes, deformations and gaps were found, which could cause difficulties in the process of learning the operation. Keywords: Internal Didactic Transposition. Division of Natural Numbers. Teaching Practice.